I capture the castle - Smith, Dodie (London Vintage, 2004)
One of the 20th Century's most beloved novels is still winning hearts! "" "I Capture the Castle" tells the story of seventeen-year-old Cassandra and her family, who live in not-so-genteel poverty in a ramshackle old English castle. Here she strives, over six turbulent months, to hone her writing skills. She fills three notebooks with sharply funny yet poignant entries. Her journals candidly chronicle the great changes that take place within the castle's walls, and her own first descent into love. By the time she pens her final entry, she has "captured the castle"-- and the heart of the reader-- in one of literature's most enchanting entertainments. This book has one of the most charismatic narrators I've ever met. -- "J.K. Rowling, author of the Harry Potter series""
Originally published : London: Heinemann 1949
Keywords: Castles -- England -- Fiction; Teenage girls; Poerty; Bildungsroman